An investigation on effective practices of green management implementation in Universiti Utara Malaysia (UUM) - Mohd Sharif, Kamal Imran; Mohamed Udin, Zulkifli; Ibrahim, Jafni Azhan; Omar, Mazni; Tan, Yee Voone (2012)
Global warming and world climate change had impacted people's life in varying degrees.Sustainable development and the greening of living habitat has increasingly become one of the most prominent agenda globally.In effort of solve these problem, Malaysia was continuously supports initiatives in implementing sustainable urban development strategies including 'green growth' and green urbanism.Development Plans in Malaysia have long recognized the need for green strategy by way of conservation, promoting green networks in urban neighbourhoods, promoting workability and sustainable public transport.The National Green Technology Policy is one of the most current platforms supporting green growth.It introduces and proposes the implementation of innovative economic instruments, as well as the establishment of effective fiscal and financial mechanisms to support the growth of green industries. Nowadays, green management can be say is an effective strategy that for carefully stewardship of natural resources, pollution control, energy efficiency, and reduces operational cost plan.